PERANCANGAN ADAPTASI CERITA RAKYAT “RANGKAYO HITAM” DALAM BENTUK KOMIK DIGITAL UNTUK MEMPERKENALKAN BUDAYA DAERAH PROVINSI JAMBI DI KALANGAN REMAJA USIA 15 – 25 TAHUN - Prasetya, Dimas; Sukmaraga, Ayyub Anshari; Nugroho, Didit Prasetyo (Sainsbertek Jurnal Ilmiah Sains & Teknologi, 2025)
Teenagers today are less interested in traditional culture. This is due to technological advancements that make the younger generation addicted to gadgets and outside culture. This threatens the existence of traditional culture. One of the threatened cultures is folklore. There are thousands of folktales throughout Indonesia that teach moral values and character education to children and adolescents. Therefore, it is important to reintroduce folklore to the younger generation by adapting it into media that is close to teenagers, namely digital media. One of the lesser-known folktales is a story from Jambi Province. One of them is entitled Rangkayo Hitam. The design of the folklore comic "Rangkayo Hitam" utilizes digital media, namely LINE Webtoon as the main media for reading stories designed by the author. Comic media was chosen because there are illustrations and dialog arranged in sequence according to the chronology of the story, and digital-based so that it can be accessed easily anytime and anywhere. The results of designing a digital comic "Rangkayo Hitam" in the form of comic illustrations with a size of 800 x 1280 pixels that have been uploaded to the LINE Webtoon application in JPG format. This comic consists of 5 episodes with a minimum of 30 panels in each episode. The author also designed supporting media in the form of t-shirts, acrylic standees, tumblers, mugs, mouse pads, acrylic keychain, hat, and poster.